EVALUATION OF THE "TEACHING SKILLS ENRICHMENT" PROGRAM THROUGH THE CONTEXT INPUT PROCESS PRODUCT (CIPP) MODEL - Suharman, Suharman; Rohman, Nur (Al-Bidayah : Jurnal Pendidikan Dasar Islam, 2022)
This study aims to evaluate the success rate of teaching skills enrichment programs in PGMI Study Programs through the CIPP program evaluation model. This research uses qualitative descriptive research methods through a case study approach in the Madrasah Ibtidaiyah STAIN Teungku Dirundeng Teacher Education Study Program, Meulaboh, West Aceh. Data collection methods through observation, interviews, and documentation. The results showed: (1) context evaluation refers to programs designed as a form of debriefing to prospective students before direct teaching practice in schools (FEP). (2) Evaluation of inputs shows full support from teaching human resources, budget funds, and facilities and infrastructure supporting activities. (3) The evaluation process shows that the teaching skills enrichment program is implemented based on three stages, namely; planning, reporting, and evaluation. (4) Product evaluation shows that the skill enrichment program produces several learning tools such as learning syllabi, lesson plans, and interactive learning media.